Association of inflammatory markers with clinical outcome in COVID-19 patients during the second wave in 100 bedded dedicated COVID MCH Hospital, Raigarh, Chhattisgarh State - Pankaj Madhukar Luka,; Ved Prakash Gilley,; Anmol Madhur Minz,; Harish Kumar,; Manoj Kumar Minj, (Asian Journal of Medical Sciences, 2024)
Background: A novel coronavirus (severe acute respiratory syndrome coronavirus 2 [SARS-CoV-2]) was the causative agent of coronavirus disease 2019 (COVID-19) pandemic 2019. SARS-CoV-2 affects respiratory tract and damages the tissue resulting in generation of inflammatory cells such as cytokines and chemokines such as IFN that damage the lung alveoli, causing severe acute respiratory syndrome. Aims and Objectives: The aims and objectives of the study are to analyze the blood inflammatory markers of COVID-19 patients and association between clinical outcomes in COVID-19-positive patients with serum inflammatory markers during the second wave of COVID-19 pandemic in 100 bedded dedicated COVID MCH Raigarh CG. Materials and Methods: In this hospital-based cross-sectional observational study, 90 patients with COVID-19 were enrolled and categorized into three groups: mild, moderate, and severe. Blood inflammatory markers such as C-reactive protein (CRP), lactate dehydrogenase (LDH), ferritin, CK-Nac as well as hemogram total leukocyte count (TLC), differential leukocyte count, and neutrophil: lymphocyte (N:L) were determined and analyzed. Results: The results of the oxygen saturation (SpO2) severity strength of association with multiple variables taken in the study through logistic regression analysis of COVID-19 patient’s inflammatory markers serum levels of LDH (P<0.05, odds ratio [OR]=1.0146), ferritin (P<0.05, OR=0.9788), N:L (P<0.05, OR=4.1041), and other non-inflammatory parameters such as creatinine (P<0.05, OR=17.8039) were significant. SpO2 severity of COVID-19 patient’s with inflammatory markers LDH, ferritin, CK-Nac, and TLC associated with all severe, moderate, and mild groups. There was no significant association in the serum levels of CRP between the severe, moderate, and mild groups. Conclusion: The findings of this study suggest that the levels of LDH, ferritin, CK-Nac, and TLC could be used to predict the severity of COVID-19 disease.